(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Article own into in students pragmatic formation of competence and him improvement technologies about theoretical and practical actions about information takes and them analysis does​ Also students​​ pragmatic meanings​​ understanding and development with engage in​ in detail explained.